2015
DOI: 10.3109/14397595.2015.1034941
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decrease in salivary epidermal growth factor levels in patients with Sjögren's syndrome: A 3-year follow-up study

Abstract: The rapid decrease in salivary EGF level contributes to the progression of intraoral manifestations of SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Oral health is an integral part of general well-being, and activities such as conversing, smiling, and eating are important determinants of daily QoL 66 . Oral health-related quality of life has been studied in patients with pSS 27,[67][68][69] and other systemic disorders [70][71][72] . Not surprisingly, using the OHIP-49 questionnaire, Lopez-Jornet et al found that patients with pSS had lower OHRQoL compared to patients with secondary SS (24.15 ± 24.34 vs 10.27 ± 14.65) 27 .…”
Section: General Health-related Quality Of Life Patients With Medicamentioning
confidence: 99%
See 1 more Smart Citation
“…Oral health is an integral part of general well-being, and activities such as conversing, smiling, and eating are important determinants of daily QoL 66 . Oral health-related quality of life has been studied in patients with pSS 27,[67][68][69] and other systemic disorders [70][71][72] . Not surprisingly, using the OHIP-49 questionnaire, Lopez-Jornet et al found that patients with pSS had lower OHRQoL compared to patients with secondary SS (24.15 ± 24.34 vs 10.27 ± 14.65) 27 .…”
Section: General Health-related Quality Of Life Patients With Medicamentioning
confidence: 99%
“…Similar findings were reported by McMillan and co-workers 67 . It has been established in several studies that patients with both pSS and sSS suffer from significantly reduced OHR QoL 27,30,[67][68][69]73 . However, research on OHRQoL in patients with non-SS sicca has been very limited.…”
Section: General Health-related Quality Of Life Patients With Medicamentioning
confidence: 99%
“…EGF, which combines with EGF receptor (EGFR) to control cell development and proliferation, is secreted from salivary glands. The clinical importance of EGF in both salivary and lacrimal glands in SS has also been discussed, as a relationship between the EGF concentration and exocrine function was demonstrated [128,129,130,131]. …”
Section: Control Of Apoptosis In Sjögren’s Syndromementioning
confidence: 99%
“…To the best of our knowledge, no study conducted to date has measured salivary EGF levels in patients with SS. Thus, we evaluated changes in salivary EGF levels in patients with SS and assessed the association between salivary EGF levels and the severity of intraoral manifestations in SS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%